(untitled) (Journal of Pharma Insights and Research, 2025)
The present research work is about an innovative technique of manufacturing chocolate by adding banana bracts (Musa paradisiaca), which helps converting agricultural waste into a value-added nutritional product. The objective of this work was to develop a dark chocolate formulation enriched with banana bract powder and evaluate its physicochemical properties, phytochemical composition, and consumer acceptance. Fresh banana bracts were processed into a fine powder and incorporated into dark chocolate at an optimized concentration of 11g per 50g of chocolate. Phytochemical screening revealed the presence of significant bioactive compounds including alkaloids, flavonoids, tannins, glycosides, and saponins in the banana bract powder. The formulated chocolate exhibited desirable physical characteristics with a melting point of 48°C, glossy appearance, and resistance to fat and sugar blooming. Sensory evaluation conducted with 52 participants demonstrated high consumer acceptance rates for taste, aroma, texture, and overall satisfaction. The chocolate maintained its structural integrity and organoleptic properties while delivering enhanced nutritional benefits through the incorporation of banana bract bioactives. The developed product represents a sustainable solution to agricultural waste utilization while offering potential health benefits associated with both dark chocolate and banana bract phytochemicals. It can be concluded from the study that functional confectionery products can be developed using agricultural by-products, contributing to both sustainability and nutraceutical food development